ERADICATION OF CORRUPTION CRIMINAL ACTS - Eko Wahyono (LPPM STAI Muhammadiyah Probolinggo, 2023)
Corruption, at its core, tends to involve the abuse of authority and power, resulting in financial losses to the state or hindrance to the national development. Thus, it is crucial to combat this issue to achieve a just and prosperous society, as envisioned by Pancasila and the Constitution of the Republic of Indonesia in 1945.To effectively eradicate corruption, the government enacted Law Number 31 of 1999 concerning the Eradication of Corruption, which was later amended through Law Number 20 of 2002 on Corruption Eradication. Despite these amendments, corruption remains prevalent and even continues to proliferate.The occurrence of corrupt practices is often linked to individuals holding public positions, acting either on their own or in collusion with corporate entities. To minimize such misconduct, it becomes essential for superiors to exercise supervision over their subordinates. Therefore, it is necessary to establish regulations that restrict opportunities for abusing their positions.The fight against corruption requires a comprehensive approach, encompassing not only legal measures but also cultural and institutional changes. By fostering a transparent and accountable governance system, Indonesia can move closer to realizing its vision of a fair and prosperous nation based on the principles of Pancasila and its constitutional foundation..